2007
DOI: 10.1593/neo.07238
|View full text |Cite
|
Sign up to set email alerts
|

Early Alterations in Ovarian Surface Epithelial Cells and Induction of Ovarian Epithelial Tumors Triggered by Loss of FSH Receptor

Abstract: Little is known about the behavior of the ovarian surface epithelium (OSE), which plays a central role in ovarian cancer etiology. It has been suggested that incessant ovulation causes OSE changes leading to transformation and that high gonadotropin levels during postmenopause activate OSE receptors, inducing proliferation. We examined the chronology of OSE changes, including tumor appearance, in a mouse model where ovulation never occurs due to deletion of follitropin receptor. Changes in epithelial cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…It is important to point out that the lack of negative feedback on LH secretion mediated by estradiol and progesterone is considered the principal reason for the high serum LH concentrations in women with PCOS [26]. As previously described in ovarian epithelial [17], theca [15] and luteal cells [43] our data demonstrate for the first time that GATA-4 and GATA-6 are expressed in preovulatory follicles from both control and PCOS women. However, the fact that the mRNA abundances for both transcription factors in PCOS follicles were similar to those in controls led us to conclude that neither GATA-4 nor GATA-6 are responsible for the altered gene expressions of the steroidogenic enzymes found in PCOS patients.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is important to point out that the lack of negative feedback on LH secretion mediated by estradiol and progesterone is considered the principal reason for the high serum LH concentrations in women with PCOS [26]. As previously described in ovarian epithelial [17], theca [15] and luteal cells [43] our data demonstrate for the first time that GATA-4 and GATA-6 are expressed in preovulatory follicles from both control and PCOS women. However, the fact that the mRNA abundances for both transcription factors in PCOS follicles were similar to those in controls led us to conclude that neither GATA-4 nor GATA-6 are responsible for the altered gene expressions of the steroidogenic enzymes found in PCOS patients.…”
Section: Discussionsupporting
confidence: 76%
“…Although it has been well established that GATA factors are expressed in ovarian tissue, their functions remain CAGCGCCTCAACAGCCACAT AAGGGCTTCTCCACGATGATGC [40] controversial. For example, it has been reported that the lack or diminution of the GATA system results in cellular dedifferentiation and ovarian tumorigenesis [16,17], whereas it has also been reported that GATA-4 is over-expressed in gonadal tumors [9]. Prostaglandins (PGs) play a fundamental role in the reproductive system [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these mice being sterile never ovulate and thus the concept of incessant ovulation does not explain the origin of ovarian cancer in these mice. Similarly, Chen et al (2007) questioned the very basis for incessant ovulation to result in ovarian cancer as more than 90% of FORKO mice develop ovarian epithelial tumors by 12 months of age, which are otherwise sterile and never ovulate . Smith & Xu (2008) have postulated that depletion of follicles and germ cells might underlie the etiology of ovarian cancers.…”
Section: Introductionmentioning
confidence: 99%
“…As knowledge of early tumorigenic events and genes is urgently needed, these issues can be studied systematically in models that can be experimentally manipulated to capture chronological changes. Thus we reported that in follitropin receptor knockout (FORKO) mice with sex hormone imbalances, females develop age-dependent ovarian tumors by B12 months (Danilovich et al, 2001;Chen et al, 2007). Tracking early and progressive ovarian tumorigenic events in this model revealed the pattern of molecular changes also found in EOC in women, including claudins, E-cadherin and platelet-derived growth factor (PDGF) ligands and receptors, as well as immune system upregulation in pretumor stages (Chen et al, 2006;Aravindakshan et al, 2006a, b).…”
Section: Introductionmentioning
confidence: 89%